THE INFLUENCE OF WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMANCE: Study of PDAM Kolaka Office Employees - Milliana; Andry Stepahnie Titing; Hendrik, Hendrik (PT. Altin Riset Publishing, 2023)
This research aims to determine the effect of work discipline and compensation on employee performance at the Kolaka district PDAM office. This research uses a quantitative method. Data collection in this research used observation, literature study, and the distribution of questionnaires. The population in this study was 70 respondents. Likewise, the sample in this study was 70 respondents using a sampling technique, namely the census method. Research instrument testing uses validity and reliability tests with SPSS 22.0. The data analysis techniques used in this research are measurement model testing (outer model) and structural model testing (inner model) with smart PLS 4.0. Based on the research results, it is known that there is a positive and significant influence between the work discipline variables, as shown by the P-value of 0.000. Meanwhile, the Compensation variable has a positive and significant effect on Employee Performance as shown by the P-Value value of 0.032.